TANTANGAN PENERAPAN SISTEM BELAJAR ONLINE BAGI MAHASISWA DITENGAH PANDEMIK COVID-19 - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata (Jurnal Ekonomi dan Bisnis (EK&BI), 2020)
The Covid-19 virus epidemic that hit Indonesia had an impact on policies in changing creative, adaptive and innovative teaching and learning processes. In preventing the spread of the covid-19 virus, the Indonesian government closed schools and universities for a while. Campus management conducts health protocols without reducing teaching and learning process between students and lecturers. One of the activities carried out on campus is by conducting online or online classes using various applications such as zoom and E-learning. This research method is done by qualitative methods. Data obtained by conducting a survey of 50 Indonesian Business Polytechnic students online. The purpose of this research is to get information about problems and obstacles faced by students when conducting the online learning process. This research is expected to be able to provide input for higher education institutions in managing and providing policies during the Covid-19 pandemic